Impaction of mandibular third molars after orthodontic treatment by the edgewise method: a retrospective study - Lucas Garcia SANTANA; Túlio Silva PEREIRA; Izabella Barbosa FERNANDES; Margareth Maria Gomes de SOUZA; Saul Martins PAIVA; Maria Leticia RAMOS-JORGE; Leandro Silva MARQUES (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract This study aimed to determine the incidence of mandibular third molar (M3) impaction after orthodontic treatment by edgewise appliances, and identify possible determinant factors of M3 impaction. A retrospective cohort study was conducted with 1154 patients. Complete orthodontic records were analyzed pretreatment and posttreatment, considering the following variables: type of Angle malocclusion, treatment with or without extraction of first premolars, overbite, stage of dentition, M3 prior angulation and duration of orthodontic treatment. Impaction was determined after radiographic evidence of total closure of the root apex. The chi-square test and Poisson regression (p < 0.05) were used for statistical analysis with a hierarchical approach. Rate ratios (RR) and 95% confidence intervals (CI) were calculated. Mandibular M3 impaction incidence was 17%. Overbite equal to or greater than 4 mm (RR = 1.23, 95%CI: 1.11-1.26, p < 0.001), prior mesial angulation of M3 (RR = 0.59, 95%CI: 0.52-0.68, p < 0.001), non-extraction of first premolars (RR=1.06, 95%CI: 1.01-1.12, P=0.019) and orthodontic treatment time equal to or less than three years (RR = 0.94. 95%CI: 0.90-0.99, p < 0.014) were significantly associated with impacted M3. There was no correlation between the type of Angle malocclusion and the risk of impaction. In conclusion, the incidence of mandibular M3 impaction was considered low. The main pretreatment factors directly involved in impaction were mesioangulation of M3 and overbite equal to or greater than 4 mm. Orthodontic treatment with extraction of first premolars and treatment time greater than 3 years reduce the risk of impaction.